TYPES OF SLANG FOUND IN SONG LOWKEY BY NIKI - Nur Aprianti Hanifah; Anita Anggraeni (PROJECT (Professional Journal of English Education), 2024)
Slang word is an informal words, phrases, and expressions that often used between people who already close to each other. Slang words often used in daily conversation in a group of people or in literary work such as book, movies, or song. In this research, the researcher attempt to analyze slang words that used in a song. Lowkey by Niki is chosen as a subject of the research. Descriptive qualitative was used in this research.The result of the research shown that there are 22 slang words found in the lyric. From 22 slang words, 4 words are considered as fresh and creative type, 7 words are categorized as flippant, 4 words are imitative type, and 7 words are classified as clipping.